Trifocal morphing - SIU, Angus M. K. (Institutional Knowledge at Singapore Management University, 2003)
Image morphing allows smooth transition between 2D images. However, one of the limitations of existing image morphing techniques is the lack of interaction - the viewpoints of the interpolated images are restrained to the line joining the optical centers of the source and the destination images. Another limitation of existing image morphing techniques is that shape warping often causes distortion due to barycentric mapping. In this paper, we present our trifocal morphing technique to address these problems. The new technique allows a user to change the viewpoint of the output images, i.e., increasing the degrees of freedom of interaction, and supports both interpolation and extrapolation. By making use of the intrinsic geometric relationship among the reference images for projective transformation, the distortion from barycentric mapping is also prevented. Unlike other warping-based view transferring techniques, trifocal morphing provides very smooth transition between reference images and supports both rigid and non-rigid scenes.